House Dust Mite Exposure: Can It Be A Severe COVID-19 Prevention? - Trasia, Reqgi First (UNUSA Press, 2022)
Background: In the midst of the ongoing COVID-19 pandemic, many studies are looking for treatment to suppress viral replication and prevention through vaccination. However, to this day the number of incidences and deaths due to COVID-19 is still increasing. Objective: The purpose of this article is to review theoretically the alleged increase in eosinophils in house dust mite exposure can prevent the severity of COVID-19 symptoms. Methods: This article was compiled through a literature search in reputable international journals by the time 2020-2021. Result: The severity of symptoms that arise due to COVID-19 infection is one of them caused by eosinophenia. On the other hand, the host immune response to house dust mite exposure can increase the number of eosinophils through stimulation of IL-6, IL-8, GM-CSF, IL-5 and IL-33. These eosinophils will then express TLR-7 on the cell surface which makes them able to recognize SARS-CoV-2. Stimulation of this eosinophil receptor triggers the production of cytokines, degranulation, superoxide, and nitric oxide (NO) through NO synthase which has a direct antiviral effect. EDN and ECP of human eosinophils can decrease viral infectivity through a ribonuclease-dependent mechanism. Eosinophils are capable of producing extracellular traps composed of eosinophilic granule proteins bound to mitochondrial DNA in response to viral infection in vitro, especially in an oxidative lung tissue environment. Eosinophils also rapidly mobilize granules of Th1 cytokines, including IL-12 and IFN-g which are important for antiviral immune responses. Conclusion: Although available data are still limited, there are indications that eosinophils have a protective effect during SARS-CoV-2 infection. Therefore, biological agents such as exposure to house dust mites targeting eosinophils may be useful to help clarify the role of eosinophils in their antiviral response.